Peri-implant disease part 1: diagnosis and assessment parameters. (2nd November 2019) - Daly, Alex; McCracken, Giles
Abstract : Where suitable, dental implants are praised as a method of providing fixed solutions with good longevity, and providing greatly improved retention for removable prostheses, resulting in increased levels of patient satisfaction and quality of life. However, with increasing evidence of long-term follow-up, there is a growing recognition of the susceptibility of dental implants to peri-implant diseases; peri-mucositis and peri-implantitis. This paper discusses the features of peri-implant disease and important aspects of assessment criteria. CPD/Clinical Relevance: This paper highlights the importance of supportive maintenance care for patients with dental implants, as well as the features and assessment of peri-implant disease.